Weighted Norm Inequalities for Fractional Bergman Operators - Sehba, B.F. (Constructive Approximation, 2019)
We prove in this paper one weight norm inequalities for some positive Bergman-type operators.
Research Article
Keywords: Békollè–Bonami weight; Bergman operator; Dyadic grid; Maximal function; Upper-half plane